PENGARUH PELATIHAN DAN MOTIVASI KERJA KARYAWAN TERHADAP KINERJA KARYAWAN PADA PT. PLN (PERSERO) AREA PEKANBARU RAYON KOTA TIMUR - Arnis Wahyuni; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
PT. PLN (Persero) Area Pekanbaru Rayon east city is a branch of PT. PLN (Persero) Region Riau and Islands Riau. PT. PLN (Persero) Area Pekanbaru Rayon east of the city is one state owned enterprises. PT. PLN (Persero) Area Pekanbaru Rayon city east is in the Dr. Soetomo number 69 peknabaru with working area starting from fifty districts ( jl. Sudirman) to the district jl. Crossing east PT. PLN (Persero) Area of the eastern city of Pekanbaru conducting the implementation of training and employee motivation is epeted to encourage morale and also improve employee ferformance.In this study in the methodology used is descriptive quantitative method which is collected throughquesioner to 42 respondent. The sample used is the PT. PLN (Persero) Area Pekanbaru Rayon City East and as a source of information is the HRD. To determine the sample used census method.Result of research and hypothesis testing showed that the partial training signifificantaffect the ferformanceof employee PT. PLN (Persero) Area Pekanbaru Rayon City East. The variabel of training and work motivation simultaneously have a significant effect on employee ferformance PT. PLN (Persero) Area Pekanbaru Rayon City East.Keywords : training, work motivation, employe ferformance, PT. PLN (Persero) Area Pekanbaru Rayon east city